FACTORS AND THEORIES FOR E-COMMERCE ADOPTION: A LITERATURE REVIEW - Haryanti, Tining; Subriadi, Apol Pribadi (International Journal of Electronic Commerce Studies, 2020)
The development of technology presents e-commerce as an alternative buying and selling place beside the offline shopping center. The growth of e-commerce globally confirms people's acceptance of e-commerce presence. Various theories of technology acceptance have been formulated to determine the factors that drive technology acceptance. The evolution of technology acceptance theory aims to overcome the problem of technology acceptance from various factors. The acceptance of e-commerce is interesting to learn as a reference to determine the right strategy in the future. This study aims to classify the journey of technology acceptance in e-commerce so that it can show the driving factors for the acceptance of e-commerce in the future. This study uses a literature review approach to the use of UTAUT theory in e-commerce. UTAUT technology acceptance theory is a combination of various previous theories. In general, technology acceptance theory uses an approach that is felt by humans. This study reveals that the technological dimension in resolving humanity is an important factor in technology acceptance. Changes in the e-commerce phase play a role in determining the factors that drive their acceptance of the community. Trust becomes an important factor at the beginning of the introduction phase of e-commerce. Meanwhile, user experience as part of the technological dimension becomes an important factor in the determination phase of e-commerce based on its market. The novelty of this research is to offer the development of technology acceptance factors on UTAUT theory. The practical contribution of research as a reference for management in the preparation of future e-commerce strategies through supporting factors for technology acceptance.